Pendayagunaan Dana Sosial Melalui Financial Technology Untuk Pemberdayaan Usaha Mikro - Sry Lestari; Annida Karima Sovia; Rani Rahman Harahap (Journal of Islamic Social Finance Management, 2026)
Micro-enterprises play a significant role in promoting economic growth; however, they continue to face challenges, including limited capital, restricted access to financing, inadequate managerial capacity, and suboptimal utilization of digital technology. This study aims to analyze the utilization of the Social Fund of Bank Sumut Sharia Branch Padangsidimpuan through Financial Technology (FinTech) to empower micro-enterprises in Padangsidimpuan City and to identify the challenges encountered in its implementation. This research employed a descriptive qualitative approach through field research. Data were collected through observations, interviews, and documentation and were analyzed descriptively. The findings indicate that the bank's social fund contributes to the empowerment of micro-enterprises by increasing business capital and improving business productivity. Nevertheless, its implementation is constrained by limited funding, insufficient public outreach, inadequate assistance, and the suboptimal use of Financial Technology in the distribution of social funds. The study concludes that optimizing the digitalization of social fund distribution is essential to enhance its effectiveness, transparency, and outreach in empowering micro-enterprises.